Glycaemic control and its associated factors in patients with type 2 diabetes in the Middle East and North Africa: An updated systematic review and meta‐analysis. (27th May 2022) - Al‐ma'aitah, Odai Hamed; Demant, Daniel; Jakimowicz, Samantha; Perry, Lin
Abstract: Aims: To examine the patient‐related factors that have been linked to glycaemic control in people living with type 2 diabetes mellitus in Middle Eastern countries. Design: A systematic review and meta‐analysis. Data Sources: A computerized search was conducted using the databases MEDLINE (via PubMed and Ovid), EMBASE, Scopus and CINAHL to identify peer‐reviewed articles published in English between 1 January 2010 and 21 May 2020. On 28 June 2021, the search was updated with the same keywords and databases; however, no further relevant studies were identified. Review Methods: Extracted data were analysed using Review Manager 5.4. Results: The final sample consisted of 54 articles with a total of 41, 079 participants. Pooled data showed an increased risk of inadequate glycaemic control in smokers [OR = 1.26, 95% confidence interval (CI): 1.05, 1.52; p = .010], obese patients (OR = 1.30, 95% CI: 1.10, 1.54; p = .002), patients with elevated waist to hip ratio (OR = 1.62, 95% CI: 1.16, 2.26; p = .004) and longer disease duration (OR = 2.01, 95% CI: 1.64, 2.48; p < .001). A lower risk of inadequate control was associated with physical activity (OR = 0.40, 95% CI: 0.24, 0.67; p < .001) and self‐management (OR = 0.49, 95% CI: 0.29, 0.82; p = .006). Conclusion: These findings highlight the opportunity to address factors to improve glycaemic control. Further longitudinal studies are required to better understand these variations, to assess all predictors of glycaemic control in participants with type 2 diabetes, and to provide a strong basis for future measures to optimize glycaemic control.